Is There a Correlation Between Coronary Artery Ectasia and Neutrophil-Lymphocyte Ratio? - Kamal Khadem Vatani (Journal of Global Pharma Technology, 2017)
Objectives: Coronary artery ectasia (CAE) has been defined as a dilated artery luminal diameter that is at least 50%greater than the diameter of the normal portion of the artery. Isolated CAE is defined as CAE without significant coronary artery stenosis and isolated CAE has more pronounced inflammatory symptoms. Neutrophil to lymphocyte ratio (NLR) is widely used as a marker of inflammation and an indicator of cardiovascular outcomes in patients with coronary artery disease. We examined a possible association between NLR and the presence of isolated CAE. Study design: The study population included 150 patients (78 male; 72 female; mean age 53.8±6.5).including 50 patients with CAE and 50 patients with coronary artery disease and 50patients with normal coronary arteries. Baseline neutrophil, lymphocyte and NLR measured at admission in all patients. Results: The NLR significantly higher in patients with CAE than dose with normal coronary arteries (2.36 ±1.16 Vs 1.44±.58 p<0.001).The isolated CAE and CAD groups were similar in terms of NLR, neutrophil counts and lymphocyte counts. Conclusion: The N/R ratio is higher in patients with CAE. This ratio is related to presence of CAE.Keywords: Coronary Artery, Neutrophil-Lymphocyte Ratio.